Strain crossing in mrigal (Cirrhinus cirrhosus): An avenue to persuade heterosis in F1 generation of wild×hatchery hybrid - Md. Ashkar Bin Sayeed (Journal of Fisheries, 2015)
While the increase of the yield of commercially trendy farmed fishes are of special priority in aquaculture, a number of handy technologies are indispensable to realize the surplus production aiming to feed the growing population. As a genetic means of doing this, hybridization technology has been being used for years, because it can produce hybrid vigor through inducing heterosis. Similar attempt was made in mrigal, Cirrhinus cirrhosus, by crossing the hatchery strain with the riverine strain to investigate the heterotic effect in the progeny the species could generate through such intra-specific hybridization. Mean fertilization and hatching rates in hybrids were found to be lower by 7% and 4% respectively than that in purebreds, which envisioned to be trivial to impact the purpose of crossing. Comparative growth test between purebreds and hybrids showed significant differences (p< 0.05) in weight and length, and resulted 30.51% heterosis in hybrid mrigal. This experiment can be considered as a preliminary investigation to motivate the application of strain crossing in mrigal farming and the result found thereof can be used as a clue to optimize this growth boosting technique for the species through further research.